2016
DOI: 10.11124/jbisrir-2016-2479
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and challenges in the use of art as an intervention for making sense of the cancer experience

Abstract: How does art contribute as a psychotherapeutic tool in making sense of the cancer experience? What is the meaningfulness of integrating art (as either creator or consumer) for patients throughout the cancer experience?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…8 Difficult and often hidden experiences are seen, heard, held, and transformed. 23 Although we identified several previous reviews on art therapy 3,[29][30][31][32] or mindfulness 1,13,15,16,19,20,[33][34][35][36] as distinct psychosocial modalities, no current or planned review on the effectiveness of MBAIs amongst adults with a physical illness were found. There was one older literature review 37 that described how mindfulness and the arts could be conceptually integrated in various populations, but it did not synthesize the research findings.…”
Section: Introductionmentioning
confidence: 99%
“…8 Difficult and often hidden experiences are seen, heard, held, and transformed. 23 Although we identified several previous reviews on art therapy 3,[29][30][31][32] or mindfulness 1,13,15,16,19,20,[33][34][35][36] as distinct psychosocial modalities, no current or planned review on the effectiveness of MBAIs amongst adults with a physical illness were found. There was one older literature review 37 that described how mindfulness and the arts could be conceptually integrated in various populations, but it did not synthesize the research findings.…”
Section: Introductionmentioning
confidence: 99%